2019
DOI: 10.1002/jmrs.317
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of exposure indicators: a pilot study of exposure technique in digital radiography

Abstract: Introduction Digital radiography lacks visual clues of exposure techniques used to obtain radiographs, therefore manufacturers have included exposure indicators (EIs). EIs provides feedback about exposure techniques used and evaluating EIs will yield much needed information about exposure trends used in digital radiography. Methods A retrospective explorative quantitative study was conducted at nine randomly selected imaging departments in Gauteng, South Africa. Data pertaining to EI was retrospectively collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The past use of radiation protection reported in the current study aligns with findings in a South African Limpopo study where only 29% of radiographers indicated using radiation protection on patients 6 . A South African study found that a quarter of patients received more radiation exposure than was necessary to produce a diagnostic radiograph 11 . Likewise, a retrospective evaluation of 100 pre‐processed neonatal chest X‐rays revealed that 77% were not collimated optimally 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The past use of radiation protection reported in the current study aligns with findings in a South African Limpopo study where only 29% of radiographers indicated using radiation protection on patients 6 . A South African study found that a quarter of patients received more radiation exposure than was necessary to produce a diagnostic radiograph 11 . Likewise, a retrospective evaluation of 100 pre‐processed neonatal chest X‐rays revealed that 77% were not collimated optimally 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in Gauteng, South Africa, revealed that only 33% of radiographers knew the function of exposure indicators 8 and a quarter of patients received more radiation exposure than was necessary to produce a diagnostic radiograph 9 . However, the reasons for South African radiographers’ radiation protection behaviour remains largely unexplored 7,8,10–12 . The theory of planned behaviour posits that behaviour depends mostly on the intention to perform a behaviour 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P7 Similarly, a study in Gauteng, South Africa, showed that 27% of patients received more radiation exposure than was necessary to produce a diagnostic radiograph. 41 A study in Ahvaz-Iran showed that 26% of reviewed examinations in the study used a mAs greater The radiation protection principles (justification, optimisation, limitation) and the application of thereof are known very well, but in the end, it is a personal choice to practice. Although they had good knowledge about the basic principles of radiation protection, poor compliance was observed.…”
Section: P11mentioning
confidence: 99%
“…29 Additionally, greater reflection may be still be required amongst practicing radiographers in order to discern good and poor practice in terms of exposure factor selection. 30 Despite several participants indicating an increasing confidence and understanding when manipulating exposures, overall, each participant found it challenging to articulate their own approach to setting and manipulating exposure parameters: John: "I assess (the patient) build and go back to the system and decrease the kV and the mA by 2 or 5".…”
Section: Selective Codingmentioning
confidence: 99%